Age and productivity of the Antarctic scallop, Adamussium colbecki, in Terra Nova Bay (Ross Sea, Antarctica) - Heilmayer, Olaf; Brey, Thomas; Chiantore, M.; Cattaneo-Vietti, R.; Arntz, Wolf (Journal of Experimental Marine Biology and Ecology, 2003)
Body size, geographical distribution and biomass make Adamussium colbecki (Smith 1902) one of the most important bivalve species in the Antarctic. Based on samples collected in austral summer 1999/2000 in Terra Nova Bay, the annual formation of shell growth bands visible on x-ray photographs was verified by stable isotope analyzis. A general von Bertalanffy growth function was fitted to size-at-age data of 25 individuals (H*= 108.86 mm, K= 0.114 y-1, t0= -0.367, D= 1.284). Maximum age of A. colbecki is likely to be more than 18 years. Somatic production calculated from mass-specific growth rates was 235 kJ m-2 y-1. Gonadal productivity estimated by an average value for reproductive output of pectinids amounted to 59 kJ m-2 y-1. Annual somatic and gonad production-to-biomass ratios (P/B) were 0.199 and 0.043, respectively. According to its consumption and production A. colbecki is likely to play a significant role in the trophic web of Terra Nova Bay.